2019
DOI: 10.1371/journal.pone.0212734
|View full text |Cite
|
Sign up to set email alerts
|

Differential prevalence and geographic distribution of hepatitis C virus genotypes in acute and chronic hepatitis C patients in Vietnam

Abstract: BackgroundThe highest burden of disease from hepatitis C virus (HCV) is found in Southeast Asia, but our understanding of the epidemiology of infection in many heavily burdened countries is still limited. In particular, there is relatively little data on acute HCV infection, the outcome of which can be influenced by both viral and host genetics which differ within the region. We studied HCV genotype and IL28B gene polymorphism in a cohort of acute HCV-infected patients in Southern Vietnam alongside two other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 54 publications
1
18
1
Order By: Relevance
“…Chronic HCV infections are often asymptomatic; it is possible that routine health care or screening for other illness identified these infections. Earlier studies reported a higher prevalence of HCV infection in men, which is contrary to our real-world data [6] . It is possible that female patients are less interested in joining research studies due to fear, stigma, or time limitations to fulfill the study requirement, including follow up visits.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Chronic HCV infections are often asymptomatic; it is possible that routine health care or screening for other illness identified these infections. Earlier studies reported a higher prevalence of HCV infection in men, which is contrary to our real-world data [6] . It is possible that female patients are less interested in joining research studies due to fear, stigma, or time limitations to fulfill the study requirement, including follow up visits.…”
Section: Discussioncontrasting
confidence: 99%
“…Genotype 3 patients had significantly higher liver enzymes, a potential marker for liver damage and high BMI, a predictor for poor treatment response. The prevalence of genotype 3 is relatively high in central region and our data is in agreement with earlier studies demonstrating a higher prevalence of genotype 3 in central highland sub-region [6] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations